Integrating complementary survey methods to estimate catches in Norway's complex marine recreational hook-and-line fishery. (23rd December 2022) - Ferter, Keno; Otterå, Håkon; Christman, Mary; Kleiven, Alf Ring; Weltersbach, Marc Simon; Gundersen, Sofie; Djønne, Christine; Bjelland, Otte; Hartill, Bruce; Lyle, Jeremy; Hyder, Kieran; Borch, Trude; et al.
Abstract: Marine recreational fishing is popular in Norway, but current estimates of the catches by resident and tourist anglers are lacking due to several challenges, in particular Norway's long and intricate coastline with no defined access points and the large tourist fishery. To test methods for long-term monitoring of boat-based marine recreational anglers, estimate their catches, and characterize the fishery, we conducted a roving creel survey based on a novel spatial sampling frame and a survey of tourist fishing businesses in Troms and Hordaland County. These surveys showed that cod ( Gadus morhua ) and saithe ( Pollachius virens ) dominated the catches in Troms, while mackerel ( Scomber scombrus ) and saithe dominated the catches in Hordaland. The estimated total annual harvest of cod by all marine recreational anglers was 2 160 tonnes (relative standard error, or RSE 44%) in Troms and 73 tonnes (RSE 29%) in Hordaland, of which ∼40% (in weight) were landed in registered tourist fishing businesses, based on data from the tourist fishing survey. The results indicate that recreational anglers in Hordaland harvest more cod in coastal waters than commercial fishers. This study provides information for developing marine recreational fisheries monitoring in challenging survey situations to support science-based fisheries management.